Osthole Attenuates Macrophage Activation in Experimental Asthma by Inhibitingthe NF-ĸB/MIF Signaling Pathway - Li, Ruyi; Song, Peng; Tang, Guofang; Wei, Jianghong; Rao, Lizong; Ma, Libing; Jiang, Ming; Huang, Jianwei; Xu, Qing; Wu, Jingjie; Lv, Qian; Yao, Dong; et al. (Frontiers in Pharmacology, 2021)
Macrophage is of significance in asthmatic airway inflammation and airway remodeling. Inhibition of activated macrophage (AM) is an altenative therapeutic strategy for asthma treatment. In this study we investigated whether coumarin compound osthole, isolated from the traditional Chinese medicine Cnidium monnieri (L.) Cuss, alleviated macrophage activaton in vivo and in vitro. Here, we reported that osthole can reduce the expression of AM marker CD206 in OVA-challenged murine asthma model. Osthole can also inhibit inflammatory infiltration, collagen deposition and inflammatory cytokines (IL-1β, TNF-ɑ, MIF) production in asthmatic mice. Similarly, In vitro, the expresson of p-IĸBɑ, MIF and M2 cytokines (Ym-1, Fizz-1, Arginase-1) in IL-4-induced macrophages decreased when exposed to NF-ĸB inhibitor MG-132. In our shRNA-MIF knockdown model, the reduced expression of M2 cytokines was also detected in IL-4+shRNA-MIF group. Osthole was able to attenuate the proliferation and migration of IL-4-induced rat alveolar macrophages NR8383 cells. Moreover, we discovered that osthole can reduce IL-4-induced NF-ĸB translocation in NR8383 cells. Collectively, our results indicated that osthole ameliorates marophage activation in asthma by suppressing NF-ĸB/MIF pathway and it might be a potential agent for treating asthma.